The Gond Painting of Prominent Artists (A Exploratory Study of Jangarh Singh Shyam, Ram Singh Urveti) - Rani, Archana (Journal of Commerce and Trade, 2019)
India's Gond tribe are renowned by art connoisseur for the vibrant artwork they produce. The Gonds also have a tradition of painting the walls and floors of their huts during important Hindu festivals. They draw scenes from religion and myth, as well as natural objects. Before mass-produced paints were available, natural pigments were used and the tribe's artwork was rarely, if ever, committed to paper. But one day in 1981, everything changed by Jangarh Singh Shyam and Ram Singh Urveti.. Before 1980s, Gond tribal art was all but unknown to outsiders, used only to decorate their homes. Forty years later, it is exhibited in galleries worldwide. This research paper attempt to study of two pioneer artists Jangarh Singh Shyam, Ram Singh Urveti ,who primarily created gond paintings on paper and canvases. This paper also discuss the life sketch and important features of the work of both artists. In their work, animals, plants and scenes from daily life are rendered in a colourful, highly patterned style comparable to aboriginal art. Classification-JEL : N35, Y50